The Monetary Approach to Exchange Rate Determination in Five ASEAN Countries - Lee, Chin (2005)
This study examines the monetary model of exchange rate determination for five ASEAN countries, namely, Indonesia, Malaysia, the Philippines, Singapore and Thailand; and to estimate their exchange rate misalignments before the 1997 currency crisis. The validity of the monetary models; the relationship between exchange rates and macroeconomic fundamentals; the restoration of the long-run equilibrium exchange rates; and the out-of-sample forecasts of monetary model were examined using vector error-correction model. The results showed that the series used are stationary and cointegrated. The likelihood ratio tests cannot reject the structural identification of the implied cointegrating relation is the sticky-price monetary model for all five ASEAN countries but rejected almost all the flexible-price monetary model and the imposed restriction of proportionality between the exchange rate and relative money. The estimated long-run parameters for Indonesia and Singapore strongly support the theory of monetary models while the result for the Philippines provides weak support. However, the long-run coefficients for Malaysia and Thailand are inconsistent with the theory. The error-correction terms are significant and correctly signed. The speeds of adjustment are rapid in Indonesia and Thailand while the speeds for Malaysia, the Philippines and Singapore are slower. Using the final parsimonious vector error-correction models, out-of-sample predictions for ASEAN five exchange rates are generated. The plotted actual and fitted exchange rates show that the models are able to track the actual exchange rate trend quiet well. The resulting residuals between the actual and the fitted values of exchange rate are the estimated misalignments. The results indicated that the Indonesia rupiah, Malaysian ringgit, Philippines peso and Singapore dollar were overvalued before the currency crisis while Thai baht was undervalued on the eve of the crisis. However, these five countries suffered modest misalignment. Therefore, little evidence of exchange misalignment is found to exist in 1997:Q2. In addition, the measure of the exchange rate valuation for ringgit Malaysia after imposing the pegging system shows that the RMAJSD exchange rate has been pegged at equilibrium level after the implementation of pegging RM3.80 to one US dollar.